Electrode material, method for producing electrode material, and secondary battery

JP7643377B2Active Publication Date: 2025-03-11TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022032159
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-02
Publication Date
2025-03-11
Estimated Expiration
2042-03-02

AI Technical Summary

Benefits of technology

【0010】 本開示の電極材料を有する二次電池は、耐久性(充放電サイクル後のクーロン効率)に優れたものとなり易い。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643377000002
    Figure 0007643377000002
  • Figure 0007643377000003
    Figure 0007643377000003
  • Figure 0007643377000004
    Figure 0007643377000004
Patent Text Reader

Abstract

To disclose an electrode material capable of improving durability of a secondary battery.SOLUTION: An electrode material contains a composite. The composite includes an Si particle, a cationic polymer layer, and an anionic polymer layer. The cationic polymer layer coats at least one part of a front surface of the Si particle. The anionic polymer layer coats at least one part of the front surface of the cationic polymer layer. The anionic polymer layer contains S as a constituent element. In the case where the front surface of the composite is analyzed by an X-ray photoelectron spectroscopy (XPS), a ratio AS / ASi of an area AS of a peak derived from 2s electron of S and an area ASi of a peak derived from 2p electron of Si is larger than 0.02 and less than 0.15.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application discloses an electrode material, a method for producing the electrode material, and a secondary battery. [Background technology]

[0002] Patent Document 1 discloses a composite having a Si material, a carbon layer covering the Si material, and a cationic polymer layer covering the carbon layer. When the composite of Patent Document 1 is used as an electrode material for an electrolyte battery, direct contact between the electrolyte and Si is suppressed, and decomposition of the electrolyte during charging and discharging of the battery can be suppressed to a certain extent. Patent Document 2 discloses an anode material that includes a core containing Si, and the surface of the core is chemically treated or coated with a predetermined material to be positively charged. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-048628 A [Patent Document 2] Special Publication No. 2015-500558 Summary of the Invention [Problem to be solved by the invention]

[0004] There is room for improvement in the durability (coulombic efficiency after charge-discharge cycles) of secondary batteries having electrode materials containing Si. [Means for solving the problem]

[0005] As one of the means for solving the above problems, the present application provides: An electrode material comprising a composite, the composite has Si particles, a cationic polymer layer, and an anionic polymer layer; the cationic polymer layer covers at least a part of the surface of the Si particle, the anionic polymer layer covers at least a portion of the surface of the cationic polymer layer; the anionic polymer layer contains S as a constituent element, When the surface of the complex is analyzed by X-ray photoelectron spectroscopy (XPS), the area A of the peak derived from the 2s electron of S S and the area A of the peak due to the 2p electrons of Si Si Ratio to A S / A Si is greater than 0.02 and less than 0.15; electrode material Disclose.

[0006] As one of the means for solving the above problems, the present application provides: Coating at least a portion of the surface of a Si particle with a cationic polymer layer to obtain a precursor; and and coating at least a portion of a surface of the cationic polymer layer of the precursor with an anionic polymer layer containing S as a constituent element to obtain a composite. When the surface of the complex is analyzed by X-ray photoelectron spectroscopy (XPS), the area A of the peak derived from the 2s electron of S S and the area A of the peak due to the 2p electrons of Si Si Ratio to A S / A Si is greater than 0.02 and less than 0.15; Manufacturing method of electrode material Disclose.

[0007] In the production method of the present disclosure, the zeta potential of the cationic polymer layer in water may be a positive potential, and the zeta potential of the anionic polymer layer in water may be a negative potential.

[0008] In the production method of the present disclosure, the difference between the zeta potential of the cationic polymer layer and the zeta potential of the anionic polymer layer may be 50 mV or more and 80 mV or less.

[0009] As one of the means for solving the above problems, the present application provides: A secondary battery having a negative electrode, an electrolyte, and a positive electrode, The negative electrode comprises the electrode material of the present disclosure. secondary battery Disclose. Effect of the Invention

[0010] A secondary battery having the electrode material of the present disclosure tends to have excellent durability (Coulombic efficiency after charge / discharge cycles). [Brief description of the drawings]

[0011] [Figure 1] 1 shows a schematic configuration of a secondary battery. [Diagram 2] 4 shows the zeta potential of the precursor powder. [Diagram 3] This shows the change in zeta potential when a Si particle is coated with a cationic polymer layer (first layer) and then with an anionic polymer layer (second layer). [Figure 4] The relationship between the peak area ratio AS / ASi and the Coulombic efficiency is shown. [Diagram 5] 4 shows the relationship between the zeta potential difference between the first and second layers and the Coulombic efficiency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] 1. Electrode material The electrode material of the present disclosure includes a composite. Here, the composite has a Si particle, a cationic polymer layer, and an anionic polymer layer. The cationic polymer layer covers at least a part of the surface of the Si particle, and the anionic polymer layer covers at least a part of the surface of the cationic polymer layer. The anionic polymer layer contains S as a constituent element. When the surface of the composite is analyzed by X-ray photoelectron spectroscopy (XPS), the area A of a peak derived from the 2s electron of S is S and the area A of the peak due to the 2p electrons of Si Si Ratio to AS / A Si is greater than 0.02 and less than 0.15.

[0013] 1.1 Complex The composite has Si particles, a cationic polymer layer, and an anionic polymer layer. The Si particles can function as an active material. The polymer layer may be for preventing direct contact between the Si particles and the electrolyte in, for example, a liquid-based battery.

[0014] 1.1.1 Si particles The Si particles are particles containing Si. The Si particles may contain simple Si or may contain a Si alloy. The Si particles may contain oxides, impurities, etc. in addition to Si and Si alloys. There is no particular limitation on the crystal structure of Si. Any Si particles that can function as an active material of a secondary battery may be used. When the Si particles are used as a negative electrode active material, carrier ions may be inserted into the Si particles during charging of the battery, causing the Si particles to expand.

[0015] The Si particles may be composed of primary particles or secondary particles. The average particle size (D50) of the Si particles may be, for example, 1 nm or more, 10 nm or more, 50 nm or more, or 100 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 10 μm or less. The average particle size (D50) is the particle size (median size) at an integrated value of 50% in a volume-based particle size distribution obtained by a laser diffraction / scattering method.

[0016] The Si particles may have voids (for example, porous). When the Si particles have voids, for example, the amount of expansion when carrier ions are inserted into the Si particles tends to be small. The porosity of the Si particles is not particularly limited.

[0017] 1.1.2 Cationic polymer layer The cationic polymer layer covers at least a part of the surface of the Si particle. Even if the surface of the Si particle is covered with the cationic polymer layer, it is possible to insert carrier ions into the Si particle, and it is also possible to desorb carrier ions from the Si particle. Usually, the surface of the Si particle is negatively charged. In this way, by covering the surface of the negatively charged Si particle with a cationic polymer layer, the cationic polymer layer is likely to follow the expansion and contraction of the Si particle due to electrostatic interaction. In addition, even if the Si particle expands and contracts, the collapse of the polymer layer is likely to be suppressed due to the elasticity of the polymer.

[0018] The cationic polymer layer is relatively positively charged compared to the Si particles. For example, the cationic polymer layer may be one whose zeta potential in water is positive (the zeta potential of the polymer constituting the cationic polymer layer in water is positive).

[0019] A variety of polymers can be used as the polymer constituting the cationic polymer layer. The cationic polymer may, for example, contain N as a constituent element, or may have a cationic group containing N. More specifically, the cationic polymer may be at least one selected from the group consisting of poly(diallyldimethylammonium chloride), polyethyleneimine, polypyrrole, and polyaniline.

[0020] The thickness and coverage of the cationic polymer layer on the surface of the Si particle are not particularly limited. However, according to the new findings of the present inventor, there is a limit to the thickness and coverage of the cationic polymer layer that can be formed on the surface of the Si particle. In other words, it is difficult to thicken the polymer layer by simply forming a cationic polymer layer on the surface of the Si particle, and it is difficult to sufficiently suppress the decomposition of the electrolyte near the surface of the Si particle. In contrast, in the composite of the present disclosure, the surface of the cationic polymer layer is further coated with an anionic polymer layer, which makes it easy to thicken the polymer layer.

[0021] 1.1.3 Anionic polymer layer The anionic polymer layer covers at least a part of the surface of the cationic polymer layer. Even if the surface of the Si particle is covered with a cationic polymer layer and an anionic polymer layer, it is possible to insert carrier ions into the Si particle through these polymer layers, and it is also possible to desorb carrier ions from the Si particle. As described above, the surface of the cationic polymer layer can be relatively positively charged. By covering the surface of such a cationic polymer with an anionic polymer layer, the anionic polymer layer is likely to follow the cationic polymer layer due to electrostatic interaction. In addition, the elasticity of the polymer makes it easy to suppress the collapse of the polymer layer. Furthermore, it is also possible to thicken the polymer layer, which is difficult to do with a cationic polymer alone.

[0022] The anionic polymer layer is relatively negatively charged compared to the cationic polymer layer. For example, the anionic polymer layer may have a negative zeta potential in water (the polymer constituting the anionic polymer layer has a negative zeta potential in water). The complex of the present disclosure may have an anionic polymer layer as the outermost layer. Furthermore, the complex of the present disclosure may have a negative zeta potential in water. For example, the zeta potential of the complex in water may be less than 0 mV, -5 mV or less, or -10 mV or less.

[0023] Various polymers can be used as the polymer constituting the anionic polymer layer. The anionic polymer contains S as a constituent element. Specifically, the anionic polymer may be at least one of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS) and polystyrenesulfonic acid.

[0024] The thickness and coverage of the anionic polymer layer on the surface of the cationic polymer are not particularly limited as long as the peak area ratio described below is satisfied. It is considered that the greater the thickness and coverage of the anionic polymer layer on the surface of the cationic polymer layer, the easier it is to suppress the contact between the Si particles and the electrolyte. However, if the anionic polymer layer is too thick, it may have a disadvantageous effect on the battery performance, such as an increase in resistance or a decrease in volume energy density. On the other hand, if the thickness or coverage of the anionic polymer layer is too small, there is a risk that the effect of the anionic polymer layer cannot be obtained sufficiently.

[0025] 1.1.4 Peak area ratio A S / A Si When the surface of the composite of the present disclosure is analyzed by X-ray photoelectron spectroscopy (XPS), the area A of the peak derived from the 2s electron of S is S and the area A of the peak due to the 2p electrons of Si Si Ratio to A S / A Si is greater than 0.02 and less than 0.15. S / A Si When the peak area ratio A is greater than 0.02, it can be said that a sufficient amount of anionic polymer layer is present in the composite, that is, the polymer layer on the surface of the Si particle is sufficiently thick. S / A Si When the peak area ratio A is less than 0.15, the anionic polymer layer is not excessively present, that is, the presence of the anionic polymer layer is unlikely to have a detrimental effect on the battery performance. S / A Si may be 0.03 or more, or 0.04 or more, and may be 0.14 or less, 0.12 or less, or 0.10 or less.

[0026] In this disclosure, the area A of the peak derived from the 2s electron of S S " is the integrated intensity of the peak from 223 eV to 233 eV in the XPS spectrum, and "the area A of the peak originating from the 2p electrons of Si" is the area A of the peak originating from the 2p electrons of Si. Si" is the integrated intensity of the peak from 95 eV to 105 eV in the XPS spectrum. The measurement conditions for XPS are as follows: (Analyzer) PHI5000 Versa probe II (ULVAC-PHI) (conditions) X-ray source: Al Kα, 15kV, 3mA Energy step: 0.1 eV Number of sweeps: 4 (Peak area calculation method) Using XPS analysis software MultiPak (manufactured by ULVAC-PHI), a baseline is drawn for each peak, and the integrated intensity (area) of each peak is obtained.

[0027] 1.1.5 Zeta potential of polymer layers As described above, in the composite of the present disclosure, a cationic polymer layer that is relatively positively charged and an anionic polymer layer that is relatively negatively charged are combined. Here, the difference between the zeta potential of the cationic polymer layer and the zeta potential of the anionic polymer layer may be, for example, 50 mV or more and 80 mV or less. When there is such a zeta potential difference, the thickness and coverage of the cationic polymer layer and the anionic polymer layer are likely to be more suitable, and the polymer layer is less likely to collapse due to electrostatic interaction, and the electrode material is likely to have better performance.

[0028] 1.2 Other materials The electrode material of the present disclosure includes the above-mentioned complex, and may further include other active materials, conductive assistants, binders, electrolytes, etc., as desired. The electrode material may also include various additives. The content of each component in the electrode material is not particularly limited and may be appropriately determined according to the desired performance. For example, the content of the above-mentioned complex may be 40% by mass or more, 50% by mass or more, or 60% by mass or more, or 100% by mass or less, or 90% by mass or less, with the entire electrode material (total solid content) being 100% by mass.

[0029] 1.2.1 Other active materials The electrode material of the present disclosure may contain other active materials in addition to the above-mentioned complex as the negative electrode active material. For example, the electrode material of the present disclosure may contain at least one selected from carbon-based active materials such as graphite and hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium and lithium alloys, etc., as other active materials. In addition to the above-mentioned complex, Si particles not covered with a polymer layer may be present. The proportion of the above-mentioned complex in the total active material contained in the electrode material of the present disclosure is not particularly limited. For example, the above-mentioned complex may account for 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more of the total active material contained in the electrode material, taken as 100% by mass.

[0030] 1.2.2 Conductive additives Examples of the conductive assistant include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, aluminum, and stainless steel. The conductive assistant may be, for example, particulate or fibrous, and the size is not particularly limited. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.

[0031] 1.2.3 Binders Examples of the binder include polyimide (PI)-based binders, butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyacrylic acid-based binders, etc. Only one type of binder may be used alone, or two or more types may be used in combination.

[0032] 1.2.4 Electrolytes Examples of the electrolyte include liquid electrolytes (electrolytic solutions) described below. As described above, in the electrode material of the present disclosure, the surfaces of the Si particles are covered with a polymer layer, which suppresses direct contact between the electrolyte and the Si particles, and tends to suppress decomposition of the electrolyte during charging and discharging. However, the electrode material of the present disclosure may contain a solid electrolyte as the electrolyte. The solid electrolyte may be any known solid electrolyte for batteries. The solid electrolyte may be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, inorganic solid electrolytes are excellent in ion conductivity and heat resistance. Examples of inorganic solid electrolytes include lithium lanthanum zirconate, LiPON, Li 1+X Al X Ge 2-X Examples of the solid electrolyte include oxide solid electrolytes such as (PO4)3, Li-SiO-based glass, and Li-Al-SO-based glass; and sulfide solid electrolytes such as Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5-GeS2. The solid electrolyte may be amorphous or crystalline. The solid electrolyte may be, for example, particulate. Only one type of solid electrolyte may be used alone, or two or more types may be used in combination.

[0033] 2. Manufacturing method of electrode material The technology of the present disclosure also has an aspect of a method for producing an electrode material. For example, the method for producing an electrode material of the present disclosure includes the following steps: First step: coating at least a part of the surface of a Si particle with a cationic polymer layer to obtain a precursor; and A second step: covering at least a part of the surface of the cationic polymer layer of the precursor with an anionic polymer layer containing S as a constituent element to obtain a composite; In the production method according to the present disclosure, when the surface of the composite is analyzed by X-ray photoelectron spectroscopy (XPS), the area A of the peak derived from the 2s electron of S may be S and the area A of the peak due to the 2p electrons of Si SiRatio to A S / A Si is greater than 0.02 and less than 0.15.

[0034] 2.1 First step In the first step, at least a part of the surface of the Si particles is covered with a cationic polymer layer to obtain a precursor. The first step may be, for example, a step of contacting a solution or dispersion containing a cationic polymer with the Si particles to attach the cationic polymer to the surface of the Si particles. The type of solvent is not particularly limited, and water or an organic solvent may be used. After contacting the solution or dispersion containing the cationic polymer with the Si particles, washing may be performed to remove excess polymer from the surface of the Si particles.

[0035] The conditions for coating the cationic polymer layer in the first step are not particularly limited. According to the knowledge of the present inventor, even if the concentration of the solution or dispersion containing the cationic polymer is high in the first step, the amount of the cationic polymer that adheres to the Si particles is limited. In other words, it is difficult to form a thick polymer layer using only the cationic polymer.

[0036] The cationic polymer used in the first step may be one that has a positive zeta potential in water, and the precursor obtained by the first step may be one that has a positive zeta potential in water.

[0037] 2.2 Second process In the second step, at least a part of the surface of the cationic polymer layer of the precursor is covered with an anionic polymer layer containing S as a constituent element, thereby obtaining a composite. The second step may be, for example, a step of contacting a solution or dispersion containing an anionic polymer with the precursor, thereby attaching the anionic polymer to the surface of the precursor. The type of the solvent is not particularly limited, and water or an organic solvent may be used. After contacting the solution or dispersion containing the anionic polymer with the precursor, washing may be performed to remove excess polymer from the surface of the precursor.

[0038] The coating conditions of the anionic polymer layer in the second step are the above peak area ratio A S / A Si The conditions for coating the anionic polymer layer may be controlled so that the zeta potential difference of the anionic polymer layer with respect to the cationic polymer layer (or the difference between the zeta potential of the precursor in water and the zeta potential of the complex in water) is 50 mV or more and 80 mV or less. For example, in the second step, the concentration of the solution or dispersion containing the anionic polymer may be adjusted to adjust the peak area ratio A S / A Si The thickness and coverage of the anionic polymer layer can be controlled so that the above requirement is satisfied.

[0039] The anionic polymer used in the second step may be one that has a negative zeta potential in water, and the complex obtained by the second step may be one that has a negative zeta potential in water.

[0040] 2.3 Other processes The manufacturing method of the electrode material of the present disclosure may include, for example, mixing the above-mentioned complex with at least one of a binder and a conductive assistant. The electrode material of the present disclosure may be in the form of a powder containing at least the above-mentioned complex, or in the form of a slurry or paste in which at least the above-mentioned complex is dispersed.

[0041] 3. Secondary battery The electrode material of the present disclosure can be employed, for example, as a negative electrode material in a liquid battery. That is, the secondary battery of the present disclosure has a negative electrode, an electrolyte, and a positive electrode, and the negative electrode contains the electrode material of the present disclosure. FIG. 1 shows a schematic configuration of a secondary battery 100 according to an embodiment. As shown in FIG. 1, the secondary battery 100 has a negative electrode 10, a separator 20, and a positive electrode 30. Each of the negative electrode 10, the separator 20, and the positive electrode 30 may be in contact with or impregnated with an electrolyte (not shown).

[0042] 3.1 Negative electrode The negative electrode 10 contains the above-mentioned electrode material. As shown in Fig. 1, the negative electrode 10 may include a negative electrode active material layer 11 and a negative electrode current collector 12. In this case, the negative electrode active material layer 11 may contain the above-mentioned electrode material.

[0043] 3.1.1 Negative electrode active material layer The negative electrode active material layer 11 contains the above-mentioned electrode material. In the negative electrode active material layer 11, the above-mentioned composite can function as a negative electrode active material. The shape of the negative electrode active material layer 11 is not particularly limited, and may be, for example, a sheet having a substantially flat surface. The thickness of the negative electrode active material layer 11 is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, 10 μm or more, or 30 μm or more, and may be 2 mm or less, 1 mm or less, 500 μm or less, or 100 μm or less.

[0044] 3.1.2 Negative electrode current collector The negative electrode collector 12 may be any of those generally used as negative electrode collectors for secondary batteries. The negative electrode collector 12 may be in the form of a foil, a plate, a mesh, a punched metal, or a foam. The negative electrode collector 12 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, a metal foil is excellent in terms of ease of handling. The negative electrode collector 12 may be made of a plurality of foils or sheets. Examples of metals constituting the negative electrode collector 12 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring reduction resistance, the negative electrode collector 12 may contain at least one metal selected from Cu, Ni, and stainless steel. The negative electrode collector 12 may have some kind of coating layer on its surface for the purpose of adjusting resistance, etc. The negative electrode collector 12 may be a metal foil or a base material on which the above metal is plated or vapor-deposited. In addition, when the negative electrode current collector 12 is made of a plurality of metal foils, some layer may be present between the plurality of metal foils. The thickness of the negative electrode current collector 12 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.

[0045] 3.2 Separator As shown in FIG. 1, a separator 20 may be disposed between the negative electrode 10 and the positive electrode 30. The separator 20 may have a function of preventing contact between the negative electrode 10 and the positive electrode 30 and holding an electrolyte solution, which will be described later. The separator may be any separator that is generally used in secondary batteries, and may be made of resins such as polyethylene (PE), polypropylene (PP), polyester, and polyamide. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer structure separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be made of a nonwoven fabric such as a cellulose nonwoven fabric, a resin nonwoven fabric, or a glass fiber nonwoven fabric. The thickness of the separator is not particularly limited, and may be, for example, 5 μm or more and 1 mm or less.

[0046] 3.3 Positive electrode 1, the positive electrode 30 may include a positive electrode active material layer 31 and a positive electrode current collector 32. In this case, the positive electrode active material layer 31 may include a positive electrode active material.

[0047] 3.3.1 Cathode active material layer The positive electrode active material layer 31 includes a positive electrode active material, and may further include an electrolyte, a conductive assistant, a binder, and the like. Furthermore, the positive electrode active material layer 31 may further include various additives. The content of each of the positive electrode active material, electrolyte, conductive assistant, binder, and the like in the positive electrode active material layer 31 may be appropriately determined according to the target battery performance. For example, the content of the positive electrode active material may be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and may be 100 mass% or less, or 90 mass% or less, with the entire positive electrode active material layer 31 (total solid content) being 100 mass%. The shape of the positive electrode active material layer 31 is not particularly limited, and may be, for example, a sheet shape having a substantially flat surface. The thickness of the positive electrode active material layer 31 is not particularly limited and may be, for example, 0.1 μm or more, 1 μm or more, 10 μm or more, or 30 μm or more, and may be 2 mm or less, 1 mm or less, 500 μm or less, or 100 μm or less.

[0048] The positive electrode active material may be any known positive electrode active material for secondary batteries. Among known active materials, a material that exhibits a potential (charge / discharge potential) for absorbing and releasing a predetermined ion that is higher than that of the above-mentioned Si particles can be used as the positive electrode active material. For example, when configuring a lithium ion battery, lithium cobalt oxide, lithium nickel oxide, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Various lithium-containing composite oxides such as O2, lithium manganate, and spinel-based lithium compounds may be used. Only one type of positive electrode active material may be used alone, or two or more types may be used in combination. The positive electrode active material may be, for example, particulate, and the size is not particularly limited. The particles of the positive electrode active material may be solid particles or hollow particles. The particles of the positive electrode active material may be primary particles or secondary particles formed by agglomeration of a plurality of primary particles. The average particle size of the particles of the positive electrode active material may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less.

[0049] The electrolyte, the conductive assistant, and the binder may be appropriately selected from those exemplified as those that may be included in the electrode material of the present disclosure. Each of the electrolyte, the conductive assistant, and the binder may be used alone or in combination of two or more.

[0050] 3.3.2 Positive electrode current collector The positive electrode collector 32 may be any of those generally used as a positive electrode collector for a secondary battery. The positive electrode collector 32 may be in the form of a foil, a plate, a mesh, a punched metal, or a foam. The positive electrode collector 32 may be made of a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of ease of handling. The positive electrode collector 32 may be made of a plurality of foils. Examples of metals constituting the positive electrode collector 32 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, and stainless steel. In particular, the positive electrode collector 32 may contain Al from the viewpoint of ensuring oxidation resistance. The positive electrode collector 32 may have some kind of coating layer on its surface for the purpose of adjusting resistance. The positive electrode collector 32 may be a metal foil or a base material on which the above metal is plated or vapor-deposited. In addition, when the positive electrode current collector 32 is made of multiple metal foils, some layer may be present between the multiple metal foils. The thickness of the positive electrode current collector 32 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.

[0051] 3.4 Electrolyte The electrolyte may contain, for example, lithium ions as carrier ions. The electrolyte may be either an aqueous electrolyte or a non-aqueous electrolyte, but non-aqueous electrolytes have particularly high performance. The composition of the electrolyte may be the same as that of electrolytes for secondary batteries. For example, an electrolyte in which a lithium salt is dissolved at a predetermined concentration in a carbonate-based solvent may be used. Examples of carbonate-based solvents include fluoroethylene carbonate (FEC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of lithium salts include LiPF6.

[0052] 3.5 Other configurations The secondary battery 100 may be one in which each of the above-mentioned components is housed inside an exterior body. Any known exterior body for a battery can be adopted as the exterior body. In addition, a plurality of secondary batteries 100 may be arbitrarily electrically connected and arbitrarily stacked to form an assembled battery. In this case, the assembled battery may be housed inside a known battery case. The secondary battery 100 may also have other obvious components such as necessary terminals. Examples of the shape of the secondary battery 100 include a coin type, a laminate type, a cylindrical type, and a square type. As described above, the secondary battery 100 may be a lithium ion secondary battery or other secondary batteries, but a higher effect can be expected when it is a lithium ion secondary battery.

[0053] 3.6 Manufacturing method of secondary batteries The secondary battery 100 can be manufactured by applying a known method. For example, it can be manufactured as follows. However, the method for manufacturing the secondary battery 100 is not limited to the following method. (1) An electrode material constituting a negative electrode active material layer is prepared. The electrode material may be in the form of a slurry dispersed in a solvent. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. The slurry is applied to the surface of a negative electrode current collector using a doctor blade or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode current collector, thereby forming a negative electrode. (2) The positive electrode active material constituting the positive electrode active material layer is dispersed in a solvent to obtain a positive electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. The positive electrode layer slurry is applied to the surface of a positive electrode current collector using a doctor blade or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode current collector, forming a positive electrode. (3) A separator is sandwiched between the negative electrode and the positive electrode to obtain a laminate having a negative electrode current collector, a negative electrode active material layer, a separator, a positive electrode active material layer, and a positive electrode current collector in this order. Other members such as terminals are attached to the laminate as necessary. (4) The laminate is housed in a battery case, and the battery case is filled with an electrolyte, and the laminate and the electrolyte are sealed in the battery case so that the laminate is immersed in the electrolyte, to produce a secondary battery. Note that the electrolyte may be impregnated into the negative electrode active material layer, the separator, and the positive electrode active material layer in the above step (3). EXAMPLES

[0054] The technology of the present disclosure will be described in more detail below with reference to examples, but the technology of the present disclosure is not limited to the following examples.

[0055] 1. Preparation of negative electrode active material (composite) 1.1 Example 1, Reference example 2 and Comparative Example 3 1 g of Si particles was dispersed in a 1 L solution containing 0.5 wt% of cationic polymer poly(diallyldimethylammonium chloride) (Sigma-Aldrich) using a homogenizer and stirred for 1 hour. The stirred solution was filtered and washed three times with 100 mL of water to remove excess polymer and obtain a precursor powder. The anionic polymer PEDOT:PSS (Sigma-Aldrich) was added at 0.02 wt% (Comparative Example 3), 0.05 wt% (Example 1), or 0.1 wt% ( reference The obtained precursor powder was dispersed in a 1 L solution containing Example 2) using a homogenizer and stirred for 1 hour. The stirred solution was filtered and washed three times with 100 mL of water to remove excess polymer, and a composite before drying was obtained. After that, it was vacuum dried at 60°C for 24 hours to obtain a composite for evaluation (Si particles coated with anionic polymer and cationic polymer).

[0056] 1.2 Comparative Example 1 The Si particles were used as they were as the negative electrode active material without being coated with a polymer layer.

[0057] 1.3 Comparative Example 2 1 g of Si particles was dispersed in a 1 L solution containing 1 wt% of cationic polymer poly(diallyldimethylammonium chloride) (Sigma-Aldrich) using a homogenizer and stirred for 1 hour. The stirred solution was filtered and washed three times with 100 mL of water to remove excess polymer and obtain a precursor powder. The obtained precursor powder was vacuum dried at 60°C for 24 hours to obtain a composite for evaluation (Si particles coated with a cationic polymer).

[0058] 2. Zeta potential measurement Si particles according to Comparative Example 1, Example 1, Reference example 2. Precursor powders according to Comparative Examples 2 and 3, and Example 1, Reference exampleEach of the composites according to Comparative Examples 2, 2, and 3 was redispersed in water, and the zeta potential of each in water was measured using a zeta potentiometer. Figure 2 shows the zeta potential of the precursor powder obtained by coating Si particles with a cationic polymer layer. Figure 3 shows the change in zeta potential when Si particles are coated with a cationic polymer layer (first layer) and then coated with an anionic polymer layer (second layer). Furthermore, the following Table 1 shows the difference in zeta potential between the first layer and the second layer.

[0059] 3. Analysis by XPS Si particles according to Comparative Example 1, Example 1, Reference example 2. For each of the composites according to Comparative Examples 2 and 3, the surface thereof was analyzed by XPS, and the area A of the peak due to the 2s electron of S was S and the area A of the peak due to the 2p electrons of Si Si Ratio to A S / A Si The results are shown in Table 1 below.

[0060] 4. Preparation of Positive Electrode In a screw cap bottle, NMP, 5 wt% butyl butyrate solution of PVdF-based binder, and LiNi as the positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (average particle size: 6 μm) and VGCF as a conductive additive were added to a container and stirred for 10 minutes with a Thinky Mixer (ARE-310, manufactured by Thinky) to obtain a positive electrode slurry. The positive electrode slurry was applied to an Al foil (manufactured by Showa Denko) by the blade method using an applicator to obtain a positive electrode coating. The obtained coating was dried on a hot plate at 80°C for 60 minutes to obtain a positive electrode.

[0061] 5. Preparation of the Negative Electrode In a screw cap, water, a polyacrylic acid binder, and Comparative Examples 1 to 3, Example 1, or Reference exampleThe Si particles or composite according to 2, and VGCF and KB as conductive assistants were added to a container and stirred for 10 minutes with a mixer (ARE-310, manufactured by Thinky) to obtain a negative electrode slurry. The negative electrode slurry was applied to a Cu foil (manufactured by Furukawa Electric) by the blade method using an applicator to obtain a negative electrode coating. The obtained coating was dried on a hot plate at 80°C for 60 minutes to obtain a negative electrode.

[0062] 6. Battery Preparation The prepared positive and negative electrodes were punched out to φ14 mm and φ16 mm, respectively, and then set in a roll press machine and pressed at 20 kN / cm. The positive electrode was then dried in a vacuum at 120 ° C and the negative electrode at 60 ° C for 24 hours. Each electrode was moved to a glove box, and 1 ml of electrolyte (1.2 M LiPF6 solution, solvent is a mixed solvent consisting of FEC:EC:EMC:DMC = 1:2:4:3 vol%) was dropped onto the negative electrode, a separator (made of PP) was laminated, 1 ml of electrolyte was again dropped, and then the positive electrode was laminated, and a coin cell was produced using an automatic coin cell caulking machine (Hosen Co., Ltd.).

[0063] 7.Charge / Discharge Test Each of the coin cells thus fabricated was charged at a constant current of 0.1C to 4.2V, then discharged at a rate of 0.1C to 2.5V, and the battery capacity at this time was recorded as the initial capacity. Then, a charge-discharge test was conducted 50 times, in which a constant current was charged at a rate of 1C to 4.2V, and then a constant current was discharged at 1C, and the average value of the coulombic efficiency for each cycle was calculated. The results are shown in Table 1 below and Figures 4 and 5. Figure 4 shows the peak area ratio A S / A Si Figure 5 shows the relationship between the zeta potential difference between the first layer and the second layer and the Coulombic efficiency.

[0064] [Table 1]

[0065] The results shown in FIGS. 2 to 5 and Table 1 reveal the following. (1) When Si particles without a polymer layer are used as the negative electrode active material of a liquid battery as in Comparative Example 1, the Coulombic efficiency of the battery is likely to decrease. This is believed to be due to the direct contact between the electrolyte and the Si particles during charging and discharging of the battery, which causes the decomposition of the electrolyte. (2) The Coulombic efficiency is improved by coating the surface of the Si particles with a cationic polymer layer as in Comparative Example 2. However, the zeta potential is saturated (FIG. 2), and it is difficult to further increase the coverage and thickness of the cationic polymer layer. (3) As in Comparative Example 3, the Coulomb efficiency may decrease even if the surface of the Si particle is coated with a cationic polymer layer and then the surface of the cationic polymer layer is further coated with an anionic polymer layer. This is considered to be due to the small difference in zeta potential between the cationic polymer layer and the anionic polymer layer (FIG. 3), the weak interaction between the cationic polymer layer and the anionic polymer layer, and the increased resistance, resulting in an adverse effect. (4) Example 1, Reference example As shown in FIG. 2, the surface of the Si particle is coated with a cationic polymer layer, and then the surface of the cationic polymer layer is coated with an anionic polymer layer. The coating conditions of the anionic polymer are adjusted to obtain a peak area ratio A S / A Si By controlling the peak area ratio A to be greater than 0.02 and less than 0.15, the Coulomb efficiency is greatly improved (Figure 4). It is believed that a high-quality coating is formed on the surface of the Si particles. S / A Si By controlling the zeta potential difference between the cationic polymer layer and the anionic polymer layer to be greater than 0.02 and less than 0.15, the zeta potential difference between the cationic polymer layer and the anionic polymer layer can be increased (FIGS. 3 and 5). Reference example In 2, it is considered that the difference in zeta potential between the cationic polymer layer and the anionic polymer layer was large, and the interaction between the cationic polymer layer and the anionic polymer layer was strong, resulting in the formation of a coating that was difficult to disintegrate.

[0066] From the above results, it can be said that a secondary battery having excellent durability can be obtained by constructing a secondary battery using an electrode material having the following configuration. (1) It contains a complex. (2) The composite has a Si particle, a cationic polymer layer, and an anionic polymer layer, the cationic polymer layer covering at least a portion of the surface of the Si particle, and the anionic polymer layer covering at least a portion of the surface of the cationic polymer layer. (3) The anionic polymer layer contains S as a constituent element, and when the surface of the composite is analyzed by X-ray photoelectron spectroscopy (XPS), the area A of the peak derived from the 2s electron of S is S and the area A of the peak due to the 2p electrons of Si Si Ratio to A S / A Si is greater than 0.02 and less than 0.15. [Explanation of symbols]

[0067] 10 negative electrode 11 Negative electrode active material layer 12 Negative electrode current collector 20 Separator 30 positive electrode 31 Positive electrode active material layer 32 Positive electrode current collector 100 Secondary battery

Claims

1. An electrode material comprising a composite, the composite has Si particles, a cationic polymer layer, and an anionic polymer layer; the cationic polymer layer covers at least a portion of the surface of the Si particle; the anionic polymer layer covers at least a portion of the surface of the cationic polymer layer; the anionic polymer layer contains S as a constituent element, the anionic polymer constituting the anionic polymer layer is at least one of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) and polystyrenesulfonic acid; When the surface of the composite is analyzed by X-ray photoelectron spectroscopy (XPS), the area A of the peak derived from the 2s electron of S is S and the area A of the peak due to the 2p electrons of Si Si Ratio A S / A Si is 0.04 or more and 0.10 or less, electrode material.

2. Coating at least a portion of the surface of a Si particle with a cationic polymer layer to obtain a precursor; coating at least a portion of the surface of the cationic polymer layer of the precursor with an anionic polymer layer containing S as a constituent element to obtain a composite; and Mixing the composite with at least one of a binder and a conductive assistant; the anionic polymer constituting the anionic polymer layer is at least one of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) and polystyrenesulfonic acid; When the surface of the composite is analyzed by X-ray photoelectron spectroscopy (XPS), the area A of the peak derived from the 2s electron of S is S and the area A of the peak due to the 2p electrons of Si Si Ratio A S / A Si is 0.04 or more and 0.10 or less, A method for producing an electrode material.

3. the cationic polymer layer has a positive zeta potential in water; The anionic polymer layer has a negative zeta potential in water. The method according to claim 2 .

4. a difference between the zeta potential of the cationic polymer layer and the zeta potential of the anionic polymer layer is 50 mV or more and 80 mV or less; The method according to claim 2 or 3.

5. A secondary battery having a negative electrode, an electrolyte, and a positive electrode, The negative electrode comprises the electrode material of claim 1. Secondary battery.

Citation Information

Patent Citations

  • Silicon composite negative electrode material, preparation method and lithium ion battery

    CN109713290A

  • Negative electrode and its manufacturing method, secondary battery and its manufacturing method

    JP2009076433A

  • Negative electrode for nonaqueous secondary battery and manufacture of the same, and nonaqueous secondary battery

    JP2014165007A

  • Positively charged silicon for lithium-ion batteries

    JP2015500558A

  • Silicon material-carbon layer-cationic polymer layer complex

    JP2016048628A